2019
DOI: 10.1002/jcpy.1108
|View full text |Cite
|
Sign up to set email alerts
|

Ceding and Succeeding: How the Altruistic Can Benefit from the Selfish in Joint Decisions

Abstract: We examine how the interplay of two partners’ interpersonal orientations (selfish vs. altruistic) in a decision‐making dyad impacts the extent to which the joint decision matches each partners’ individual a priori preferences. Two experiments, in which we manipulate and measure interpersonal orientations, as well as examine real consumption decisions, demonstrate the benefit of mismatching interpersonal orientations (selfish‐altruistic) in dyadic decisions. Specifically, altruistic and selfish consumers reach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Joint goal pursuit is characterized by situations whereby multiple individuals work toward a common group‐level goal (Fishbach & Tu, 2016; Weingart & Weldon, 1991). Joint decision making assumes input from all parties to arrive at a decision outcome (Greenhalgh & Chapman, 1995; Lowe et al., 2019). While some joint‐consumption situations might involve joint goal pursuit and/or joint decision making, in the current research we focused on situations in which a consumer is unilaterally making a choice for another person, and the consumer will join the recipient in consuming the chosen option—this conceptualization is consistent with that of Liu et al (2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Joint goal pursuit is characterized by situations whereby multiple individuals work toward a common group‐level goal (Fishbach & Tu, 2016; Weingart & Weldon, 1991). Joint decision making assumes input from all parties to arrive at a decision outcome (Greenhalgh & Chapman, 1995; Lowe et al., 2019). While some joint‐consumption situations might involve joint goal pursuit and/or joint decision making, in the current research we focused on situations in which a consumer is unilaterally making a choice for another person, and the consumer will join the recipient in consuming the chosen option—this conceptualization is consistent with that of Liu et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…We predicted and found in Study 7 that participants chose a goal-inconsistent product for another person in the joint-consumption condition-that is, a condition in which participants read that they would engage in the chosen activity together with their friend. It is important to clarify how joint consumption conceptualized here is different from other related consumption contexts: joint decision making (e.g., Greenhalgh & Chapman, 1995;Lowe, Nikolova, Miller, & Dommer, 2019) and joint goal pursuit (e.g., Fishbach & Tu, 2016). Joint goal pursuit is characterized by situations whereby multiple individuals work toward a common group-level goal (Fishbach & Tu, 2016;Weingart & Weldon, 1991).…”
Section: Joint Consumptionmentioning
confidence: 99%
“…These interesting dynamics have led to research on how evaluation is affected by the relative standing of individuals within the DMU. When members within a DMU differ in their preferences, the weight that each member’s preferences receive is based on influence within the DMU (Lowe et al 2019). Garbinsky and Gladstone (2019) found that couples who pooled finances in a joint bank account were more likely to choose utilitarian products when spending from that joint account than when spending from a separate account, due to the need to justify the decision.…”
Section: Traveling the Social Customer Journeymentioning
confidence: 99%
“…The contributions of this research are fourfold. First, Lowe et al (2019) called for future research to move beyond personal consumer preference and extend research toward interpersonal orientation. This study contributes toward DT and consumer literature by uncovering the underlying mechanisms influencing the behavior of DT consumers.…”
mentioning
confidence: 99%